Effect of the interaction between alcohol and meat consumption on the hyperlipidaemia risk among elderly individuals: Evidence from Shanghai, China - Huang, Xiaojing; Hui, Hong; Zhu, Wenqing; Chen, Ning; Wei, Yan; Wang, Zhaoxin; Shi, Jianwei (Frontiers in Nutrition, 2022)
Background: Diet and other lifestyle habits may have an increased effect on blood lipids of older people. This study aimed to examine the associations between diet (meat, fish, and egg), alcohol consumption and blood lipids. Methods: Surveillance data on chronic diseases and their risk factors were collected from Shanghai during 2017-2018. A Kish table was used for sampling 438 older adults, of whom 71 consumed alcohol. Logistic regression was used to test the relationships between diet, alcohol consumption and blood lipid levels in elderly individuals, and the marginal effects (MEs) were estimated. Results: Dyslipidaemia was more common among drinkers than among nondrinkers (P<0.01). Alcohol consumption was associated with dyslipidaemia (OR=2.667, P<0.01 for TC; OR=1.919, P<0.05 for LDL; OR=3.412, P<0.01 for TG), and consumption of more than 50 g of meat per day showed similar associations (OR=3.227, P<0.01 for TC; OR=3.263, P<0.01, for LDL; OR=2.329, P<0.01 for TG). The MEs of alcohol drinking and excessive meat consumption on the rate of dyslipidaemia were 0.324 for TC (P<0.01), 0.255 for LDL (P<0.05), and 0.174 for TG (P<0.01). Discussion: The risk of hyperlipidaemia was increased in elderly individuals with excessive meat and alcohol consumption, which also had an interactive effect.